Indonesia: HUBUNGAN TINGKAT PENGETAHUAN REMAJA TENTANG COVID-19 DENGAN KEPATUHAN MENERAPKAN PROTOKOL KESEHATAN DI DESA KUTUH - Sri Rahayuni; Ni Kadek Neza Dwiyanti; Ni Ketut Noriani (STIKes Buleleng, 2022)
Background: The Covid-19 pandemic has become an event that threatens public health in general and has attracted worldwide attention. On January 30, 2020, WHO (World Health Organization) has declared the COVID-19 pandemic a public health emergency of international concern. This pandemic is very disturbing and creates fear in the wider community globally and the Indonesian people are no exception.Objective: This study aims to determine the relationship between Adolescent Knowledge Levels about Covid-19 and Compliance with Implementing Health Protocols in Kutuh Village.Methods: type of observational research with cross sectional design. conducted in Kutuh Village. The sample is teenagers aged 10-19 years in Kutuh Village from October to November 2021. The data obtained includes a description of the level of knowledge and adherence of adolescents in implementing health protocols. The number of samples was 52 teenagers who were selected by the total sampling method. Data was collected using a questionnaire sheet, namely through a google form. The data was analyzed by Chi square to determine the relationship between Adolescent Knowledge Levels About Covid-19 and Compliance with Implementing Health Protocols.Results : The results of the study after the Chi-Squere Test was carried out on the knowledge variable to get a p-value of 0.007 so that the p-value <0.05. Based on statistical tests, it can be found that there is a significant relationship between the relationship between the level of knowledge of adolescents about COVID-19 and compliance with implementing health protocols in Kutuh Village.Keywords: Knowledge Level, Youth, Prokes Compliance, Covid-19